2010
DOI: 10.1186/1471-2482-10-13
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double-blinded single-site control study comparing blood loss prevention of tranexamic acid (TXA) to epsilon aminocaproic acid (EACA) for corrective spinal surgery

Abstract: BackgroundMultilevel spinal fusion surgery has typically been associated with significant blood loss. To limit both the need for transfusions and co-morbidities associated with blood loss, the use of anti-fibrinolytic agents has been proposed. While there is some literature comparing the effectiveness of tranexamic acid (TXA) to epsilon aminocaproic acid (EACA) in cardiac procedures, there is currently no literature directly comparing TXA to EACA in orthopedic surgery.Methods/DesignHere we propose a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 24 publications
0
31
0
3
Order By: Relevance
“…EACA seemed to be more effective as a method for blood loss reduction as the complexity of the surgery increased. 19 Recently, Verma et al 13 conducted a prospective, doubleblinded, randomized control trial comparing the use of TXA, EACA, and placebo used intraoperatively in patients undergoing surgery for adolescent idiopathic scoliosis. They found that TXA and EACA were both effective at reducing total blood loss, but not transfusions.…”
Section: Antifibrinolyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…EACA seemed to be more effective as a method for blood loss reduction as the complexity of the surgery increased. 19 Recently, Verma et al 13 conducted a prospective, doubleblinded, randomized control trial comparing the use of TXA, EACA, and placebo used intraoperatively in patients undergoing surgery for adolescent idiopathic scoliosis. They found that TXA and EACA were both effective at reducing total blood loss, but not transfusions.…”
Section: Antifibrinolyticsmentioning
confidence: 99%
“…60 The accepted dosing for TXA is 10 mg/kg as a loading dose, with 1 mg/kg/hr for maintenance until incision closure, while the dosing for EACA is 100 mg/kg as loading dose, with 10 mg/kg/hr for maintenance until incision closure. 13 In the pediatric surgical literature, TXA doses as high as 100 mg/kg as a loading dose with 10 mg/kg/hr maintenance have been explored. 61 The ideal dose and duration of TXA for pediatric and adult scoliosis patients remains debated and is a direction for future study.…”
Section: Antifibrinolyticsmentioning
confidence: 99%
“…8 During the prospective trial 125 patients were randomized to Tranexamic acid (TXA), Aminocaproic acid (EA-CA), or Saline (control) for surgery from January 2009 to January 2011. Level-1 data from this homogeneous population minimizes the effect of confounding variables.…”
Section: Populationmentioning
confidence: 99%
“…All patients in the prospective study had a complete blood count drawn just prior to incision. 8 Of the 125 patients enrolled in that study: 28 patients donated blood prior to surgery (PD group), 97 patients did not pre-donate blood (Non-PD group). …”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation